Hubungan Pernikahan Dini Dengan Kejadian Baby Blues Syndrome Di Desa Sidetapa - Diantari, Komang Sri; Parwati, Ni Wayan Manik; Haryati, Ni Putu Sri (STIKES Karya Husada Kediri, 2025)
The postpartum period involves many changes, both physical and psychological. Mothers may experience feelings of sadness related to their baby, a condition known as postpartum blues or baby blues. The purpose of this study is to determine the relationship between early marriage and the incidence of baby blues syndrome in young mothers. Since the postpartum period requires comprehensive care, there are times when mothers experience feelings of sadness related to their baby, referred to as baby blues syndrome. This study is an observational analysis utilizing a cross-sectional approach.This research was conducted in Sidetapa Village, Banjar District, Buleleng Regency, Bali, from October to November 2024, using a total sampling technique with 45 respondents. The data collection tool employed was the Edinburgh Postnatal Depression Scale (EPDS) questionnaire. The analysis utilized the Spearman's Rho statistical test. The results of the study were gathered from 45 surveyed individuals; the majority were aged 20-35 years, totaling 21 individuals (46.7%), 25 individuals had completed high school (55.6%), 29 individuals were unemployed (64.4%), 40 individuals earned less than the minimum wage (88.9%), 27 individuals were primipara (having given birth once) (60%), 33 individuals were married before the age of 20 (73.3%), and 31 individuals experienced baby blues syndrome (68.9%).The results of the statistical test using Spearman Rho, with a p-value of 0.000, are less than the established threshold of < 0.05, thus Ha is accepted. There is a relationship between early marriage and the incidence of baby blues syndrome among young mothers in Sidetapa Village, Banjar District, Buleleng Regency.